PERAN CHANGE COMMUNICATION STRATEGIES PADA PENGEMBANGAN BISNIS LAUNDRY - Dwi Amelia Sitorus, Shinta; Sandika Mariani, Seftiana; Natanael Purba, Vieri; Dia Nofita Sari, Rini; Luna Azaria, Theresia; Persada Dewangga Pramudita, Dismas (Penerbit Lafadz Jaya, 2025)
This study explores the role of change communication strategies in the development of a laundry business, a micro-enterprise operating in the service sector. The main issue addressed is how the business owner communicates service changes to customers and internal partners to ensure acceptance and business continuity. The objective is to analyze the communication strategies used and their effectiveness in building customer understanding and loyalty. This qualitative research employs direct interviews and field observations, with the business owner as the primary data source. The findings reveal that communication strategies are implemented directly, informally, and participatively, both toward customers and the owner's spouse as an internal business partner. Face-to-face communication is preferred as it is considered clearer, more personal, and effective in explaining changes such as service additions or pricing adjustments. Furthermore, a dialogic approach between the owner and spouse facilitates faster decision-making regarding business innovations. The study concludes that open and contextual change communication strategies strengthen trust, reduce resistance, and support business growth in an ever-changing environment.